2018
DOI: 10.21206/rbas.v8i3.3011
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho Agronômico De Cultivares De Alface Sob Adubação Orgânica Em Seropédica, Rj

Abstract: O objetivo do presente trabalho foi avaliar o efeito da aplicação de bokashi, esterco bovino, e da combinação entre estes, sobre o crescimento e produtividade de nove cultivares de alface (Lactuca sativa L.) nas condições de Seropédica-RJ. O ensaio foi realizado em condições de campo no período de setembro a outubro de 2017. Utilizaram-se como tratamentos quatro tipos de adubação, sendo: bokashi (0,5 kg/m2); mistura de bokashi com esterco bovino (0,250 kg/m2 +1,0 kg/m2, respectivamente); adubação com esterco b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Esses resultados corroboram com os obtidos por Souza LH, et al, (2016), que constataram melhor desempenho da alface crespa com o emprego de 0,5kg/m 2 de bokashi. Goulart RGT, et al, (2018) avaliando o efeito da aplicação de bokashi (0,5kg/m 2 ), esterco bovino (1,0kg/m 2 ) e da combinação destes (0,250kg/m 2 de bokashi + 1,0kg/m 2 de esterco bovino) sobre o crescimento e produtividade de alface, concluíram que a mais eficaz foi o bokashi, que resultou em maior crescimento e produtividade das plantas.…”
Section: Resultsunclassified
“…Esses resultados corroboram com os obtidos por Souza LH, et al, (2016), que constataram melhor desempenho da alface crespa com o emprego de 0,5kg/m 2 de bokashi. Goulart RGT, et al, (2018) avaliando o efeito da aplicação de bokashi (0,5kg/m 2 ), esterco bovino (1,0kg/m 2 ) e da combinação destes (0,250kg/m 2 de bokashi + 1,0kg/m 2 de esterco bovino) sobre o crescimento e produtividade de alface, concluíram que a mais eficaz foi o bokashi, que resultou em maior crescimento e produtividade das plantas.…”
Section: Resultsunclassified
“…Bokashi compost triggered greater development in lettuce (Brito et al, 2002;Goulart et al, 2018). The number of pods of green beans was higher when Penergetic was applied (Brito et al, 2012); increased yields were also found for sugar beet (Jakiene et al, 2009) and radish (Hata et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…EM (Effective Microorganisms) Bokashi was tested with several vegetables with promissory results. For lettuce, diameter, fresh biomass and number of leaves was increased by using Bokashi at 500 g m -2 (Goulart et al, 2018). Beetroot (Beta vulgaris L.) and cabbage (Brassica oleracea var.…”
Section: Bokashi Compost and Biofertilizer Increase Lettuce Agronomic Variables In Protected Cultivation And Indicates Substrate Microbiomentioning
confidence: 99%
“…This unique composition allows the integration of the biofertilizer in a mixture with the substrate [25], promoting seed germination and the development of high-quality seedlings, in addition to contributing to obtaining satisfactory yields in various crops [26,27]. Bokashi-type formulations show a positive influence on the yield and quality of diverse agricultural crops [28], exhibiting promising outcomes in beet and cabbage cultivation [29,30], as well as tomato [31], lettuce [32], and radish [33].…”
Section: Introductionmentioning
confidence: 99%